A catalyst ni / zr-mcm-41, its preparation method and plasma catalytic application thereof

CN116637646BActive Publication Date: 2026-10-20FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310436700.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-21
Publication Date
2026-10-20
Estimated Expiration
2043-04-21

AI Technical Summary

Technical Problem

[0007]本发明提供了一种催化剂Ni/Zr-MCM-41及其制备方法和等离子体催化应用,主要目的是解决Ni基负载型催化剂在高温反应中不稳定、易烧结和因积碳而失活的技术问题

Benefits of technology

[0059](1)本发明采用介孔分子筛MCM-41作为载体,制备出高稳定、抗积碳的Ni/Zr-MCM-41催化剂;与常规氧化物载体相比,表面生成的层状硅酸镍物种提高了Ni活性位点的分散度,阻碍了活性金属颗粒在高温下迁移和烧结,减少了积碳的产生。本发明在介孔分子筛MCM-41中引入了金属Zr,插入SiO2框架的Zr4+对Ni2+的锚定效应强于MCM-41载体,强金属-载体相互作用是其优异稳定性的主要原因;同时,载体中加入的Zr4+可吸附和活化CO2,减少积碳尤其是惰性碳的生成。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116637646B_ABST
    Figure CN116637646B_ABST
Patent Text Reader

Abstract

The application discloses a catalyst Ni / Zr-MCM-41, a preparation method thereof and plasma catalytic application, and belongs to the technical field of chemical materials. The catalyst Ni / Zr-MCM-41 comprises a carrier and an active component; the carrier comprises Zr-MCM-41; the active component comprises a metal nickel element; and the metal nickel element is distributed on the inner and outer surfaces of the Zr-MCM-41 in the form of layered nickel silicate. The Ni / Zr-MCM-41 catalyst is used for a plasma-promoted CO2 and CH4 dry reforming reaction, and synthesis gas is obtained, so that CO2 emission reduction and reuse are realized; the catalyst has excellent catalytic activity, high stability, sintering resistance and carbon deposition resistance, and the conversion rates of CO2 and CH4 do not have obvious inactivation phenomena within 50 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of chemical materials technology, and particularly relates to a catalyst Ni / Zr-MCM-41, its preparation method, and its plasma catalytic application. Background Technology

[0002] Carbon dioxide (CO2) and methane (CH4) are major greenhouse gases. In recent decades, the rapid increase in atmospheric CO2 concentration has led to a series of environmental problems, such as climate change, ocean acidification, glacial melting, and global warming. Due to the urgent need to address these environmental issues and reduce greenhouse gas emissions, dry reforming (DRM) of CO2 and CH4 has received widespread attention as a promising technology. The syngas produced by dry reforming is an important feedstock for Fischer-Tropsch synthesis and other chemical reactions.

[0003] Because dry reforming is a strongly endothermic reaction, traditional thermocatalytic dry reforming requires temperatures above 700°C. From an industrial application perspective, high temperatures lead to a series of problems, including high energy consumption, high costs, and equipment wear and tear. Therefore, high-temperature reaction conditions are a significant factor hindering the further large-scale application of CO2 and CH4 dry reforming reactions.

[0004] Dielectric barrier discharge (DBD) plasma offers a promising alternative to traditional thermocatalytic reactions due to its unique non-equilibrium characteristics. Compared to conventional thermocatalytic processes, DBD reactors can generate a series of high-energy electrons at ambient temperature and pressure, which then undergo inelastic collisions with charged particles and free radicals dissociated from gas molecules. This fundamentally alters the catalytic reaction process and initiates thermodynamically unfavorable reactions at low temperatures without requiring additional heat input. Therefore, DBD plasma can serve as a transformative technology for lowering the temperature of dielectric barrier discharge (DRM) reactions.

[0005] Besides its high endothermic nature, another major challenge hindering the development of the DRM reaction is the lack of catalysts with good stability and strong resistance to carbon deposition. Developing catalysts with high activity, high selectivity, high stability, and low cost is crucial for the activation and conversion of inert molecules CO2 and CH4. Noble metals (Ru, Rh, Pd, and Pt) have been studied, and their catalysts exhibit high catalytic performance in dry reforming reactions. However, due to their low reserves and high prices, they are unsuitable for large-scale industrial applications. Furthermore, high temperatures exacerbate various side reactions, such as CH4 decomposition and CO disproportionation, leading to the formation of large amounts of carbon deposits covering the active metal surface, clogging the reactor, and hindering the long-term stable operation of the DRM reaction.

[0006] Therefore, developing novel catalysts with well-defined structures and obtaining catalysts with both excellent catalytic performance and resistance to carbon deposition, as well as long-term catalytic stability, is of great significance for promoting the further development of CO2 and CH4 dry reforming reactions. Summary of the Invention

[0007] This invention provides a catalyst Ni / Zr-MCM-41, its preparation method, and its plasma catalytic application. The main purpose is to solve the technical problems of instability, easy sintering, and deactivation due to carbon deposition in Ni-based supported catalysts during high-temperature reactions.

[0008] On one hand, the present invention provides a catalyst Ni / Zr-MCM-41, the catalyst comprising a support and an active component; the support comprising Zr-MCM-41; the active component comprising metallic nickel; the metallic nickel being distributed in the form of layered nickel silicate on the inner and outer surfaces of the Zr-MCM-41.

[0009] Optionally, Zr is Zr 4+ The form and Ni in the layered nickel silicate 2+ Mutually anchored.

[0010] Optionally, in the carrier Zr-MCM-41, Zr is Zr 4+ It is inserted into the SiO2 framework of MCM-41 in the form of [insertion].

[0011] Optionally, the carrier Zr-MCM-41 is a Zr-modified mesoporous molecular sieve MCM-41.

[0012] Optionally, the carrier Zr-MCM-41 is obtained by hydrothermal synthesis using a silicon source, a zirconium source, and a surfactant.

[0013] Optionally, the zirconium source includes zirconium nitrate; the silicon source includes tetraethyl orthosilicate; and the surfactant includes hexadecyltrimethylammonium bromide.

[0014] Optionally, the nickel loading is 2% to 10%, based on the mass percentage of the catalyst.

[0015] Optionally, the nickel loading is 3% to 6% by mass of the catalyst.

[0016] Optionally, the nickel species on the Zr-MCM-41 surface have a particle size of 3–20 nm.

[0017] Optionally, the nickel species on the Zr-MCM-41 surface have a particle size of 4–10 nm.

[0018] Optionally, the pore size of the mesoporous molecular sieve MCM-41 is 1.5 nm to 30 nm.

[0019] Optionally, the pore size of the mesoporous molecular sieve MCM-41 is 2 nm to 8 nm;

[0020] Optionally, the pore size of the mesoporous molecular sieve MCM-41 is selected from any value or a range between any two of the following: 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, and 30 (all in nm).

[0021] Optionally, the pore size of the mesoporous molecular sieve MCM-41 is 4 nm.

[0022] Optionally, the specific surface area of ​​the mesoporous molecular sieve MCM-41 is 100 m². 2 / g~1000m 2 / g.

[0023] Optionally, the specific surface area of ​​the mesoporous molecular sieve MCM-41 is selected from 100 m² / g, 200 m² / g, and 300 m² / g. 2 / g、400m 2 / g、500m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g, 1000m 2 Any value in / g or any range between the two.

[0024] The mesoporous material selected in this invention is an important catalyst support in catalytic reactions. Its porous structure is conducive to the adsorption of reactant gas molecules and can enhance the activation and transformation of reactants.

[0025] On the one hand, the metal active center exists in the form of layered nickel silicate, and the presence of Si-O-Ni bonds restricts the further growth of the metal during the reaction process, preventing the catalyst from sintering and deactivating.

[0026] On the other hand, mesoporous materials typically possess high specific surface areas, and a large number of metal-support interfaces enhance metal-support interactions, thereby increasing the stability of metal particles. Mesoporous molecular sieve MCM-41, with its ordered hexagonal mesoporous structure, high specific surface area, adjustable pore size, and heteroatom composition, is an ideal support for loading metal nanoparticles.

[0027] This invention introduces metallic Zr into mesoporous molecular sieve MCM-41, with Zr inserted into the SiO2 framework. 4+ For Ni 2+The anchoring effect of Zr is stronger than that of the MCM-41 support, and the strong metal-support interaction is the main reason for its excellent stability; at the same time, Zr 4+ The addition of [the substance] significantly enhances CO2 adsorption and activation, reducing the formation of carbon deposits, especially inert carbon.

[0028] This invention uses mesoporous molecular sieve MCM-41 as a support to prepare a highly stable Ni / Zr-MCM-41 catalyst that is resistant to carbon deposition. Compared with conventional oxide supports, the layered nickel silicate species generated on the surface of the molecular sieve improve the dispersion of Ni active sites, hinder the migration and sintering of active metal particles at high temperatures, and reduce the generation of carbon deposits.

[0029] Secondly, the present invention provides a method for preparing the above-mentioned catalyst, the method comprising the following steps: (S1): obtaining mesoporous molecular sieve Zr-MCM-41 as a support;

[0030] (S2): The mesoporous molecular sieve Zr-MCM-41 support and the nickel-ammonia complex solution are subjected to an ammonia stripping process to obtain a molecular sieve catalyst preparation;

[0031] (S3): The molecular sieve catalyst preparation in step (S2) is washed, dried and calcined to obtain mesoporous molecular sieve Ni / Zr-MCM-41.

[0032] Optionally, the mesoporous molecular sieve Zr-MCM-41 in step (S1) is obtained by hydrothermal synthesis using a silicon source, a zirconium source, and a surfactant.

[0033] Optionally, the molar ratio of the silicon source, the zirconium source, and the surfactant is 10:1:1.

[0034] Optionally, the silicon source is derived from tetraethyl orthosilicate; the zirconium source is derived from zirconium nitrate; and the surfactant includes hexadecyltrimethylammonium bromide.

[0035] Optionally, the nickel in the nickel-ammonia complex solution in step (S2) comes from nickel nitrate solution and the ammonia comes from ammonia water;

[0036] The reaction mass percentage of nickel nitrate with the mesoporous molecular sieve Zr-MCM-41 is 2% to 10%.

[0037] Optionally, the reaction ratio of nickel nitrate to the mesoporous molecular sieve Zr-MCM-41 is 0.1g to 0.5g: 5g.

[0038] Optionally, the temperature for ammonia stripping in step (S2) is 50℃~100℃, and the time for ammonia stripping is 3h~12h.

[0039] Optionally, the temperature for ammonia stripping in step (S2) is 60℃~80℃, and the ammonia stripping time is 4h.

[0040] Optionally, the temperature for ammonia stripping is selected from any value of 50°C, 60°C, 70°C, 80°C, 90°C, and 100°C, or a range between any two.

[0041] Optionally, the ammonia stripping time is selected from any value of 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or any range between two.

[0042] Optionally, the calcination in step (S3) is carried out in an air atmosphere, and the calcination temperature is 300℃~800℃, with a heating rate of 1℃ / min~10℃ / min.

[0043] Optionally, the calcination in step (S3) is carried out in an air atmosphere, and the calcination temperature is 300℃~800℃, with a heating rate of 1℃ / min~10℃ / min.

[0044] Optionally, the calcination in step (S3) is carried out in an air atmosphere, and the calcination temperature is 500℃~600℃, with a heating rate of 2℃ / min.

[0045] Optionally, the roasting temperature is selected from any value or a range between 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, and 800℃.

[0046] Optionally, the heating rate is selected from any value of 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min or a range between any two.

[0047] Optionally, the drying is vacuum drying, the vacuum drying temperature is 20℃-200℃, and the vacuum drying time is 8h-12h.

[0048] Optionally, the drying is vacuum drying, the vacuum drying temperature is 20℃-200℃, and the vacuum drying time is 8h-12h.

[0049] Optionally, the temperature of the vacuum drying is selected from any value of 20℃, 50℃, 80℃, 100℃, 120℃, 150℃, 180℃, 200℃ or a range between any two.

[0050] Optionally, the vacuum drying time is selected from any value of 8h, 9h, 10h, 11h, 12h or any range between two.

[0051] Thirdly, the present invention provides the application of the above-mentioned catalyst Ni / Zr-MCM-41 in plasma-promoted dry reforming reactions of CO2 and CH4.

[0052] Fourthly, the present invention provides a method for preparing syngas, comprising: under plasma discharge conditions, contacting the raw material gas CO2 with CH4 and the catalyst Ni / Zr-MCM-41 to undergo a catalytic reaction to obtain syngas; wherein the catalyst Ni / Zr-MCM-41 is the above-mentioned catalyst Ni / Zr-MCM-41 or the catalyst Ni / Zr-MCM-41 prepared by the above method.

[0053] Optionally, the reaction volume ratio of CH4 to CO2 is 0.5 to 2; the reaction pressure of the catalytic reaction is 0.1 MPa, the reaction temperature is 100℃ to 500℃, and the plasma discharge power is 0 to 120 W.

[0054] Optionally, the reaction volume ratio of CH4 to CO2 is selected from any value of 0.5, 0.8, 1.0, 1.2, 1.5, 1.8, 2.0 or any range between two.

[0055] Optionally, the temperature of the catalytic reaction is selected from any value or a range between 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, and 500°C.

[0056] Optionally, the plasma discharge power is any value or a range between 0W, 10W, 20W, 30W, 40W, 50W, 60W, 70W, 80W, 90W, 100W, 110W, and 120W.

[0057] Optionally, the plasma discharge is achieved using a dielectric barrier discharge plasma reactor.

[0058] Compared with the prior art, the present invention has the following beneficial effects:

[0059] (1) This invention uses mesoporous molecular sieve MCM-41 as a support to prepare a highly stable Ni / Zr-MCM-41 catalyst with resistance to carbon deposition. Compared with conventional oxide supports, the layered nickel silicate species formed on the surface improve the dispersion of Ni active sites, hinder the migration and sintering of active metal particles at high temperatures, and reduce carbon deposition. This invention introduces metallic Zr into the mesoporous molecular sieve MCM-41, and the Zr inserted into the SiO2 framework... 4+ For Ni2+ The anchoring effect is stronger than that of the MCM-41 support, and the strong metal-support interaction is the main reason for its excellent stability; at the same time, the Zr added to the support 4+ It can adsorb and activate CO2, reducing the formation of carbon deposits, especially inert carbon.

[0060] (2) The present invention uses the ammonia stripping method to prepare Ni / Zr-MCM-41 catalyst, which has high dispersion and small particle size of active components. Compared with the traditional impregnation method, the ion exchange process helps the active metal to adhere firmly to the surface of the support and form a strong metal-support interaction with the molecular sieve framework.

[0061] (3) This invention employs a dielectric barrier discharge plasma reactor to achieve low-temperature conversion of CO2 and CH4, avoiding carbon deposition and sintering of active metals at high temperatures. Compared with the high-temperature conditions of traditional thermocatalytic dry reforming, this process can break through thermodynamic barriers, improve energy utilization efficiency, significantly reduce the energy cost of the dry reforming process, and generate a plasma-catalyst synergistic effect, thus achieving higher catalytic performance.

[0062] (4) The Ni / Zr-MCM-41 catalyst of the present invention is used for plasma-promoted dry reforming of CO2 and CH4 to obtain syngas, thereby achieving CO2 emission reduction and reuse. The catalyst has excellent catalytic activity, high stability, sintering resistance and anti-coking performance, and there is no obvious deactivation of CO2 and CH4 conversion rate within 50 hours. Attached Figure Description

[0063] Figure 1 This is a transmission electron microscope image of the ordered mesoporous molecular sieve MCM-41 provided in Embodiment 1 of the present invention;

[0064] Figure 2 Example 2 of this invention provides small-angle XRD and wide-angle XRD for different catalysts;

[0065] Figure 3 These are the stability test results of the catalyst of Example 3 of the present invention in the plasma-promoted dry reforming reaction of CO2 and CH4;

[0066] Figure 4 This is the TG curve of the catalyst provided in Example 2 of this invention after 50 hours of continuous evaluation. Detailed Implementation

[0067] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0068] Unless otherwise specified, the raw materials and experimental equipment used in the embodiments of this application were purchased commercially, and the experimental methods used were conventional methods.

[0069] Example 1 (Preparation of Zr-MCM-41 carrier)

[0070] Zr-MCM-41 support was prepared by hydrothermal synthesis using hexadecyltrimethylammonium bromide as a surfactant, tetraethyl orthosilicate and zirconium nitrate as Si and Zr sources respectively, in a molar ratio of 10:1:1.

[0071] Figure 1 In the figure, a and b are the uniformly distributed hexagonal pore structures of MCM-41 in Comparative Example 1 at different magnifications, indicating that the hydrothermally prepared MCM-41 molecular sieve has a regularly ordered hexagonal pore structure and a long-range ordered structure.

[0072] Figure 1 In the figure, c and d represent the uniformly distributed hexagonal channel structure of Zr-MCM-41 in Example 1 at different magnifications, which shows that Example 1 still retains the regular hexagonal channel structure of the molecular sieve after incorporating Zr into the MCM-41 molecular sieve.

[0073] Figure 1 The results (abcd) show that Zr successfully entered the interior of the MCM-41 molecular sieve and connected with the framework without damaging the pore structure of MCM-41.

[0074] Figure 1 In the figure, e and f are electron micrographs of the comparative example 2Ni / MCM-41 at different magnifications. No Ni species were observed on the support surface, which may be due to the highly dispersed state of Ni species or the small particle diameter of Ni species. g, h, i and j are HAADF-STEM and EDX mapping images of Ni / MCM-41, indicating that Ni species are uniformly dispersed in the mesoporous molecular sieve support.

[0075] Example 2 (AF) (Preparation of Ni / Zr-MCM-41 catalyst by ammonia stripping method)

[0076] A certain amount of Ni salt (nickel nitrate) was dissolved in 30 mL of deionized water to prepare a solution. Ammonia was slowly added dropwise until the solution pH was 10-11, and the solution was sealed and stirred. 5 g of mesoporous Zr-MCM-41 (Zr-MCM-41 support prepared in Example 1) was weighed and stirred for 12 h. Ammonia was evaporated by heating in a 70 °C oil bath. When the solution was neutral, it was washed by centrifugation with deionized water. After vacuum drying at 80 °C for 12 h, it was calcined in air. The differences between Examples 2A-2F are the raw material reaction ratio, ammonia evaporation temperature and calcination temperature. The prepared catalysts are labeled as 2A#, 2B#, 2C#, 2D#, 2E# and 2F#, respectively. See Table 1 for details.

[0077] Table 1. Experimental data for the preparation of Ni / Zr-MCM-41 catalyst

[0078]

[0079] Example 3 (AF) (Dry reforming reaction of CO2 and CH4)

[0080] Six catalysts prepared in Example 2 were taken in equal mass and placed in a dielectric barrier plasma reactor. The temperature of the tube furnace was adjusted to the reaction temperature. The gas was switched to a mixture of CO2 and CH4. After the reaction, the mixed gas was entered into a gas chromatograph to detect the concentration of each component and the conversion rate of CO2 and CH4 was calculated. The differences between Examples 3A-3F are that the reaction temperature of CO2 and CH4 to generate syngas under the catalysis of the catalyst is different, the plasma discharge power is different, and the catalyst is different (catalysts 2A#, 2B#, 2C#, 2D#, 2E#, and 2F# are used in 3A-3F respectively). The experimental data are detailed in Table 2.

[0081] Table 2. Experimental data for catalytic synthesis gas

[0082]

[0083] Comparative Example 1 (Catalyst used: MCM-41)

[0084] The difference between Comparative Example 1 and Example 3D is that the catalyst used is MCM-41 without Ni metal loading, and the plasma discharge power is different.

[0085] Comparative Example 2 (Catalyst used: Ni / MCM-41 via ammonia stripping process)

[0086] The difference between Comparative Example 2 and Example 3D is that the catalyst used is Ni / MCM-41 prepared by the ammonia stripping method.

[0087] Comparative Example 3 (Catalyst used: Impregnated Ni / MCM-41)

[0088] The difference between Comparative Example 3 and Example 3D is that the catalyst used is Ni / MCM-41 prepared by impregnation method.

[0089] Figure 2 In the figure, a represents the small-angle XRD patterns of MCM-41 in Comparative Example 1, Ni / MCM-41 prepared by the ammonia stripping method in Comparative Example 2, and Ni / Zr-MCM-41 prepared in Example 2; this shows that the prepared catalysts have the characteristic diffraction peaks of MCM-41 and maintain a hexagonal mesoporous structure.

[0090] Figure 2 In the diagram, b and ac are wide-angle XRD patterns of Ni / Zr-MCM-41 catalysts with loadings of 2%, 5%, and 10%, respectively, and d is the Ni / MCM-41 catalyst prepared by the impregnation method.

[0091] analyze Figure 2 Results: In the catalyst prepared by the ammonia stripping method, Ni exists in the form of layered nickel silicate species, while in the catalyst prepared by the impregnation method, Ni mainly exists in the form of NiO.

[0092] Depend on Figure 2 It can be seen that the nickel element on the Ni / Zr-MCM-41 catalyst prepared by the present invention is uniformly distributed in the interior of the Zr-MCM-41 molecular sieve as layered nickel silicate; while the nickel element in the Ni / MCM-41 prepared by the impregnation method in Comparative Example 3 is distributed in the interior of the MCM-41 molecular sieve as nickel oxide.

[0093] analyze Figure 3 The catalyst preparation conditions are shown in Example 2D in Table 1, and the catalyst evaluation conditions are shown in Example 3D in Table 2. The Ni loading in Ni / MCM-41 and Ni / Zr-MCM-41 is 6%. The catalyst stability evaluation temperature is 500℃ and the time is 50 hours.

[0094] Depend on Figure 3 It can be seen that the CO2 conversion rate of Ni / Zr-MCM-41 prepared by this invention is still relatively high after 50 hours of catalysis, followed by Ni / MCM-41 (ammonia stripping method), and Ni / MCM-41 (impregnation method) is the worst.

[0095] Compared to Ni / MCM-41 (ammonia stripping method), the CO2 conversion rate of Ni / MCM-41 (impregnation method) increased by 43.5% after the ammonia stripping method was adopted. Compared to Ni / Zr-MCM-41 (ammonia stripping method), the CO2 conversion rate increased by 18.5% due to the incorporation of Zr.

[0096] Accordingly, the catalyst stability evaluation is as follows: Ni / Zr-MCM-41 (ammonia stripping method) > Ni / MCM-41 (ammonia stripping method) > Ni / MCM-41 (impregnation method).

[0097] Figure 3 Analysis results: The Ni / Zr-MCM-41 catalyst exhibited the highest catalytic activity and stability, indicating that Zr... 4+ The addition of [a specific ingredient] significantly improved the stability of the catalyst.

[0098] As can be seen from the experimental data in Table 2:

[0099] A comparison between Example 3D and Comparative Example 1 shows that the conversion rate of Ni / Zr-MCM-41 used in Example 3D of this invention is Con.(CO2) = 75.5% and Con.(CH4) = 69.9%; while the conversion rate of MCM-41 used in Comparative Example 1 is Con.(CO2) = 28.1% and Con.(CH4) = 22.6%. This demonstrates that the MCM-41 catalyst, which does not contain nickel and zirconium metal elements, has a very low conversion rate for the synthesis reaction, poor catalyst activity, and severe carbon deposition during sintering.

[0100] A comparison between Example 3D and Comparative Example 2 shows that although both catalysts were prepared using the ammonia stripping method, the conversion rates of Ni / MCM-41 in Comparative Example 2 (Con.(CO2) = 73.5%, Con.(CH4) = 64.7%) were lower than those of Ni / Zr-MCM-41 in Example 3D of this invention. This demonstrates that adding zirconium to Ni / MCM-41 can improve the catalytic performance of the catalyst.

[0101] A comparison between Example 3D and Comparative Example 3 shows that the conversion rate of the Ni / MCM-41 catalyst prepared by the impregnation method in Comparative Example 3 is Con.(CO2) = 60.4% and Con.(CH4) = 48.2%, which is also lower than the Ni / Zr-MCM-41 conversion rate in Example 3D of this invention; this proves that inserting zirconium into Ni / MCM-41 can improve the catalytic activity of the catalyst.

[0102] Depend on Figure 4 It can be seen that, compared with Ni / MCM-41, the amount of carbon deposited on the Ni / Zr-MCM-41 catalyst after the reaction is less, indicating that incorporating Zr into the molecular sieve Ni / MCM-41 can improve the stability and anti-carbon deposition performance of the catalyst.

[0103] Comparative Examples 2 and 3 were prepared using different methods to produce Ni / MCM-41. The catalyst performance of Comparative Example 2 was higher than that of Comparative Example 3, demonstrating that the catalyst prepared by the ammonia stripping method was more effective than the impregnation method.

[0104] By analyzing the experimental data and experimental diagrams on CO2 conversion rate, stability, and anti-coking performance, it is demonstrated that the Ni / Zr-MCM-41 catalyst of the present invention has high stability, excellent anti-coking and sintering resistance, and high conversion rate in CO2 and CH4 dry reforming reactions.

[0105] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing syngas, comprising: Under plasma discharge conditions, the feed gas CO2 reacts with CH4 and the catalyst to produce syngas; The catalyst is characterized in that it comprises a support and an active component; the support comprises Zr-MCM-41; and the active component comprises metallic nickel. The metallic nickel element is distributed in the form of layered nickel silicate on the inner and outer surfaces of the Zr-MCM-41; In the carrier Zr-MCM-41, Zr is Zr 4+ The form and Ni in the layered nickel silicate 2+ Mutually anchored.

2. The method for preparing syngas according to claim 1, characterized in that, In the carrier Zr-MCM-41, Zr is Zr 4+ It is inserted into the SiO2 framework of MCM-41 in the form of [insertion].

3. The method for preparing syngas according to claim 1, characterized in that, The carrier Zr-MCM-41 is a Zr-modified mesoporous molecular sieve MCM-41.

4. The method for preparing syngas according to claim 1, characterized in that, The carrier Zr-MCM-41 was obtained by hydrothermal synthesis using silicon source, zirconium source and surfactant.

5. The method for preparing syngas according to claim 4, characterized in that, The zirconium source includes zirconium nitrate; the silicon source includes tetraethyl orthosilicate; and the surfactant includes hexadecyltrimethylammonium bromide.

6. The method for preparing syngas according to claim 1, characterized in that, The nickel loading is 2% to 10%, based on the mass percentage of the catalyst.

7. The method for preparing syngas according to claim 1, characterized in that, The nickel loading is 3% to 6%, based on the mass percentage of the catalyst; The nickel species on the Zr-MCM-41 surface have a particle size of 3 to 20 nm.

8. The method for preparing syngas according to claim 6 or 7, characterized in that, The nickel species on the Zr-MCM-41 surface have a particle size of 4 to 10 nm.

9. The method for preparing syngas according to claim 3, characterized in that, The method for preparing the catalyst includes the following steps: (S1): Obtain mesoporous molecular sieve Zr-MCM-41 as a support; (S2): The mesoporous molecular sieve Zr-MCM-41 support and the nickel-ammonia complex solution are subjected to an ammonia stripping process to obtain a catalyst preparation; (S3): The catalyst preparation in step (S2) is washed, dried and calcined to obtain the mesoporous molecular sieve catalyst Ni / Zr-MCM-41.

10. The method for preparing syngas according to claim 9, characterized in that, The mesoporous molecular sieve Zr-MCM-41 described in step (S1) is obtained by hydrothermal synthesis using silicon source, zirconium source and surfactant.

11. The method for preparing syngas according to claim 10, characterized in that, The molar ratio of the silicon source, the zirconium source, and the surfactant is 10:1:

1.

12. The method for preparing syngas according to claim 10 or 11, characterized in that, The silicon source is derived from tetraethyl orthosilicate; the zirconium source is derived from zirconium nitrate; and the surfactant includes hexadecyltrimethylammonium bromide.

13. The method for preparing syngas according to claim 9, characterized in that, In step (S2), the nickel in the nickel-ammonia complex solution comes from nickel nitrate solution and the ammonia comes from ammonia water; the mass percentage of the reaction between the nickel nitrate and the mesoporous molecular sieve Zr-MCM-41 is 2%~10%.

14. The method for preparing syngas according to claim 9, characterized in that, The temperature for ammonia stripping in step (S2) is 50 ℃~100 ℃, and the time for ammonia stripping is 3 h~12 h.

15. The method for preparing syngas according to claim 9, characterized in that, The calcination in step (S3) is carried out in an air atmosphere for 6 hours, the calcination temperature is 300℃~800℃, and the heating rate is 1℃ / min~10℃ / min; the drying is vacuum drying, the vacuum drying temperature is 20℃-200℃, and the vacuum drying time is 8h-12h.

16. The method for preparing syngas according to claim 1, characterized in that, The reaction volume ratio of CH4 to CO2 is 0.5 to 2; the reaction pressure of the catalytic reaction is 0.1 MPa, the reaction temperature is 100 ℃ to 500 ℃, and the plasma discharge power is 30 to 120 W.

17. The method for preparing syngas according to claim 1, characterized in that, The plasma discharge is achieved using a dielectric barrier discharge plasma reactor.

Citation Information

Patent Citations

  • Device for directly synthesizing C1-C4 alcohol by CH4 / CO2 at low temperature and synthesis method thereof

    CN109603707A

  • Nickel silicate-derived catalyst for producing xylitol by hydrogenation of xylose as well as preparation and application of nickel silicate-derived catalyst

    CN112916011A